Analysis of digital wallet acceptance factors and market potentials among college students - Rama, Adilla Meitri; Rahadian, Dadan (BISMA (Bisnis dan Manajemen), 2022)
One of the fintech products is a digital wallet, an electronic money service in the form of a mobile application that can use for payment transactions. This study aims to determine the acceptance factor and potential of the digital wallet market by university students. The theory used in this study is the UTAUT2 model, with performance expectancy (PE), effort expectancy (EE), social influence (SI), facilitating conditions (FC), hedonic motivation (HM), price value (PV), habit (HA) as the independent variables. Meanwhile, behavioural intention (BI) and use behaviour (UB) are dependent variables. The population in this study were all university students, while the sample was 400 people. This study collected data by distributing online questionnaires. The sampling technique used is random sampling, and the data analysis technique used is PLS-SEM with the help of SmartPLS 3.2.9 software. This study proves that the influence of the independent variables on the dependent variables is significant. In contrast, the variable effort expectancy (EE), social influence (SI), facilitating conditions (FC), and hedonic motivation (HM) were weak predictors of behavioural intention (BI). The results of this study are supposed to be useful for government and digital wallet companies to improve the market potential level of digital wallets by optimising the function of the factors that affect the use of the digital wallet. In contrast to other studies, this study investigates all the many kinds of digital wallets that operated in Indonesia, which becomes the novelty of this research.